Pharmacologically triggered hydrogel for scheduling hepatitis B vaccine administration - Gübeli, Raphael J.; Schöneweis, Katrin; Urban, Stephan (Scientific reports, 2013)
The simplification of current vaccine administration regimes is of crucial interest in order to further sustain and expand the high impact of vaccines for public health. Most vaccines including the vaccine against hepatitis B need several doses to achieve protective immunization. In order to reduce the amount of repetitive injections, depot-based approaches represent a promising strategy. We present the application of novobiocin-sensitive biohybrid hydrogels as a depot for the pharmacologically controlled release of a vaccine against hepatitis B. Upon subcutaneous implantation of the vaccine depot into mice, we were able to release the vaccine by the oral administration of the stimulus molecule novobiocin resulting in successful immunization of the mice. This material-based vaccination regime holds high promises to replace classical vaccine injections conducted by medical personnel by the simple oral uptake of the stimulus thereby solving a major obstacle in increasing hepatitis B vaccination coverage.
Gesehen am 16.02.2021